Assistance in the Implementation of Muzara'ah Contracts in Optimizing Village Land Management Based on Islamic Economics - Zainul Anwar; Misba Huddin; Imroatus Sholiha; M. Rivqi Amin; Nanda Hidayan Sono (Konsienti : Community Services Journal, 2025)
The limited optimization of village land utilization is one of the challenges faced by communities in increasing economic productivity based on local potential. This community service activity aims to assist in the implementation of the muzara'ah contract as a model of agricultural cooperation between Village-Owned Enterprises (BUMDes) and farmers in optimizing village land management based on Islamic economics. The activity implementation method uses a participatory action research (PAR) approach through the stages of problem identification, development of a cooperation model, assistance in contract implementation, and program evaluation. The results of the activity indicate that the implementation of the muzara'ah contract can improve village land utilization, strengthen cooperative relationships between BUMDes and farmers, and provide community understanding of profit-sharing mechanisms in accordance with sharia principles. This program also has a positive impact on increasing productivity and economic empowerment of village communities. Thus, the muzara'ah model can be an alternative strategy for village asset management that is oriented towards economic justice and sustainability.